Implementasi Deep Learning pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti - Baydarus, Moh.Himami; Zuhroh, Siti Aminatuz; Ma'rufin Adhar, Bintang; Ilzam Ramadani, Dida (Tarbiyatuna Kajian Pendidikan Islam, 2026)
Education in Indonesia is currently undergoing a major transformation to adapt to the demands of the 21st century, in which skills such as critical thinking, creativity, and collaboration have become key focal points. This study aims to examine the planning of Islamic Religious Education and Character Education learning based on deep learning at SMP Negeri 1 Salatiga, to analyze the implementation of deep learning–based Islamic Religious Education and Character Education at SMP Negeri 1 Salatiga, and to evaluate the learning assessment of Islamic Religious Education and Character Education based on deep learning at SMP Negeri 1 Salatiga.This research employs field research with a qualitative case study approach. Data were collected through observations, interviews, and documentation at SMP Negeri 1 Salatiga.The results indicate that the learning planning is designed contextually through the “3A” strategy (Activation–Action–Assessment). The implementation of learning integrates Islamic values with creative activities such as the “Creative Charity” project, the “This Week’s Good Deeds” project, the “Digital Charity” project, the “Collaborative Islamic Drama” project, the “Silent Kindness” project, the “Moral Safari” project, and the “Daily Gratitude Journal” project. In addition, learning activities utilize “spiritual detective” illustrations, short oral expression formats of “opinion–reason–example,” the questioning before teaching technique, the curious corner technique, the use of mind mapping or graphic organizers, and the “Reflective Concept Map” strategy.Evaluation is conducted comprehensively through diagnostic, formative, and summative assessments that not only measure cognitive aspects but also assess the holistic development of students’ character.